Chemico-pharmacological evaluation of the methanolic leaf extract of Catharanthus ovalis: GC–MS/MS, in vivo, in vitro, and in silico approaches - Shahriar, Saimon; Shermin, Samia Akter; Hasnat, Hasin; Hossain, Faisal; Han, Aixia; Geng, Peiwu; Alam, Safaet; Mamun, Abdullah Al (Frontiers in Pharmacology, 2024)
Natural plant-based medicines have gained popularity recently as a major source of inventive, riskfree, and more potent secondary bioactive compounds with medicinal potential. Catharanthus ovalis is a penial shrub containing various indole alkaloids cultivated extensively for local medical purposes. The research is conducted to identify the phytocompounds present in leaves of C. ovalis, and its central and peripheral analgesic, thrombolytic, and membrane-stabilizing activities through tail immersion, acetic acid-induced writhing, human blood clot lysis, and erythrocyte lysis by heat and hypotonic solution methods, respectively. A total of 39 compounds were identified by GC-MS/MS techniques, including Hexadecanoic acid, methyl ester (56.749%), Methyl stearate (29.782%), Carvacrol, and TBDMS derivative (12.586%), and 9-Octadecenoic acid, methyl ester, (E)-] (9.297%) presented in high quantity. The highest tail immersion latency was observed for 600 mg/kg extract of C. ovalis crude extract. Both 400 and 600 mg/kg doses of C. ovalis crude extract exhibited prominent peripheral analgesic activity. The maximum thrombolytic effect was observed by DCM soluble fraction extract by inhibiting 54.87% of the clot. However, the aqueoussoluble fraction of this extract manifested an excellent membrane stabilizing effect by showing 73.98 and 87.51% hemolysis against heat and hypotonic-induced hemolysis, respectively. Some of the compounds were identified as active against different receptors related to this disease, which supported the findings of in vitro and in vivo tests. Further investigation needs to be conducted to specify and identify the exact mechanism of action of these compounds.